2007
DOI: 10.1523/jneurosci.4163-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Lobe and Episodic Memory: Bilateral Damage Causes Impaired Free Recall of Autobiographical Memory

Abstract: Does the parietal lobe have a critical role in memory?The neuroimaging literature indicates that it has an important role, especially in episodic memory. However, the neuropsychological literature suggests that its role is more limited to attentional, spatial, or imagery aspects of memory. Here, we present data to adjudicate this disagreement. Two patients with bilateral parietal lobe damage received detailed assessments of their autobiographical memories. The results show that although both patients easily re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
293
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(315 citation statements)
references
References 56 publications
(80 reference statements)
22
293
0
Order By: Relevance
“…Those previous behavioral findings imply that scale‐invariance is a form of self‐similarity in that the holistic pattern can exist at multiple levels of magnification [and even across different memory systems, e.g., Maylor, 2002]. Here, our data affirmed the importance of the posterior parietal cortex in both immediate and long‐term retrieval [Berryhill et al, 2007, 2011] and further characterized its involvement in dealing with the spatial relations of objects within scenes [Bricolo et al, 2000; Buiatti et al, 2011]. Our data also demonstrated such short‐/long‐term correspondence exists in the precuneus/angular gyrus for temporal order retrieval (cf.…”
Section: Discussionsupporting
confidence: 86%
“…Those previous behavioral findings imply that scale‐invariance is a form of self‐similarity in that the holistic pattern can exist at multiple levels of magnification [and even across different memory systems, e.g., Maylor, 2002]. Here, our data affirmed the importance of the posterior parietal cortex in both immediate and long‐term retrieval [Berryhill et al, 2007, 2011] and further characterized its involvement in dealing with the spatial relations of objects within scenes [Bricolo et al, 2000; Buiatti et al, 2011]. Our data also demonstrated such short‐/long‐term correspondence exists in the precuneus/angular gyrus for temporal order retrieval (cf.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with neuropsychological studies showing that patients with parietal lesions reported ABMs that lacked episodic richness (Berryhill et al, 2007;Davidson et al, 2008). With regard to the role of the parietal cortex in episodic memory, the current findings can be interpreted in light of the dual attentional processes hypothesis (Cabeza, 2008;Ciaramelli et al, 2008), which distinguishes between the role of dorsal and ventral parietal regions.…”
Section: Neuropsychological Predictors Of the Proportion Of Internal supporting
confidence: 91%
“…The intact performance on the recall experiments -employing the same stimuli and encoding tasks as in the recognition experiments -signify that information was accurately encoded. These same patients were also tested on a detailed autobiographical memory test and deficits were observed for information that was encoded long before they incurred parietal lesions, once again, indicating impaired memory retrieval (Berryhill et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We were able to identify to patients with bilateral parietal lobe damage in our database. These patients have been discussed previously (Berryhill, Phuong, Picasso, Cabeza, & Olson, 2007); we summarize their profiles here.…”
Section: Participantsmentioning
confidence: 99%